The inhibitory Effect of Lactobacillus bulgaricus against some Pathogenic and Toxin Producing Fungi which isolated from soil - Luay B. Mustafa; Karkaz M. Thalij (Tikrit Journal of Pure Science, 2023)
This study was aimed to isolation and identification of  Lactobacillus delubricii subsp. bulgaricus species and to study the effect of bacterial cells at different degrees of temperature and pH levels or its metabolite products on Inhibition effects against some pathogenic and toxin produced fungi species that's isolated in laboratory. The results was found to identify Lb. delubricii subsp. bulgaricus species were isolated from dairy products and this identification was depended on morphological, cultural and biochemical characters, also were  identified four species from fungi were isolated from soil Mycrosporium canis, Trichophyton mentagrophytes , Aspergillus fumigatus and Rhizopus stolinfer. The results also was explored the effects of Lb. delubricii subsp. bulgaricus when cultivated on different pH level and temperature degree and were found the best pH level for inhibition of fungi species growth was at 6.5 and the inhibition zone diameter was 22, 24, 26 and 24 mm respectively, while the 30 C° was get the best inhibition degree for the best inhibition and the inhibition zone diameter against the fungi species was became 22, 24, 26 and 24 mm respectively. The results showed that the best pH levels to and the zone inhibition diameter against the fungi species in this study. The results was also illustrated the effects of the metabolites produced from the Lb. delubricii subsp. bulgaricus at 10 , 20 and 40 mg / ml from cultural media on the Inhibition ability to fungi , and that’s appears as significantly increased with the metabolite concentration increased and became at the 40 mg, the inhibition zone diameter was found as 32, 30, 28 and 18mm respectively